Cruising fundamentals - Munns, Harry (International Marine Pub. McGraw-Hill, 1991)
Written to complement the ASA's teaching methods, Cruising Fundamentals addresses small-boat daysailors who wish to move on to overnight cruising in a larger boat-one more than 27 feet long. The book leads the reader through five progressively more advanced levels of boat handling, each divided into sections covering knowledge and techniques that can be learned ashore and those best learned underway. A chapter called "Sailing the Cruising Yacht, " for example, presents important information on readying the boat for sail, VHF radio protocol, and right-of-way rules before examining such topics as heaving-to and steering a compass course. This effective and logical progression makes the book a great learning tool not just for those graduating from smaller to larger sailboats or from daysailing to cruising, but for inactive sailors needing a refresher and for anyone planning bareboat charter. The volume includes material on all aspects of piloting, maneuvering under power, managing the galley, diesel maintenance, passagemaking, and anchoring.